Biosorption Of Colour In Landfill Leachate By Using Base Pre-Treatment Hydrilla SP - Abdullah, Siti Nur Shafiqah Rosslan (Universiti Sains Malaysia, 2022)
Biosorbent from plant origin is still not widely applied in wastewater treatment. Its usage in leachate treatment has not been reported to date. This study examined the efficiency of Base Pre-treated Hydrilla in removing colour contaminants from landfill leachate. Leachate was collected at the Alor Pongsu Landfill Site (APLS), which was first characterised. A particle size range of 1.18 mm to 600 mm was chosen. Various adsorbent concentrations, dosage, pH and contact time values were evaluated in batch tests. The optimum concentration occurred at 1.0M. Humin acid in the leachate sample affected the adsorption efficiency. The optimum dosage was found at 1.0 g/L. It increased with increasing biosorbent dosage until it reached the equilibrium point due to the increase in the number of sorption sites and surface area. The optimum pH of the biosorption was 8. The interaction between cationic and anionic charges between sorbate and sorbent increases the adsorption efficiency, but it also affects the hydrolysis of peptide bonds if pH > 11. This study found the optimum of 60 min contact time. This is probably due to the larger number of binding sites on the cellular surface during the initial biosorption process. FTIR analysis shows that hydrilla contains -OH, -COOH and -NH groups where the attraction electrostatic occurred. This study found the surface area and pore volume slightly higher after treatment. The maximum zeta potential values (pHzc) determined was -50.8 mV at pH 10 and -55.2 mV at pH 8, before and after treatment, respectively. The equilibrium data were well fitted using the Freundlich is far superior to the Langmuir isotherm models followed the pseudo-second-order model, which revealed a relatively low and ineffective efficiency in this investigation. The current findings demonstrate that hydrilla was not a good biosorbent for colour removal in landfill leachate as it contributes its own colour to the sample. Its usage for metal treatment is recommended in future studies.